ANALISIS PENGARUH CELEBRITY ENDORSE TERHADAP BRAND IMAGE SABUN MUKA POND’S MEN ENERGY CHARGE (STUDI PADA KONSUMEN PENGGUNA SABUN MUKA POND’S MEN ENERGY CHARGE SANTRI PESANTREN MAHASISWA AL-HIKAM MALANG ANGKATAN 2015-2018) - Muhammad Farid Rohmatulloh; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to analyze the influence of celebrity endorse which consists of visibility, credibility, attraction and power towards the brand image of Pond's face soap energy charge. The method used in this study is quantitative with a sample selection of 74 users of Pond's face soap energy charge. The technique used in sample selection is purposive sampling, Data collection uses a questionnaire with a Likert scale.Analysis of the data used in this study is the analysis of linear regression tests using SPSS tools. Based on this study, states that the credibility variable has a significant effect on brand image (p-value 0,000 <0,05) and attraction variable have a significant effect on brand image (p-value 0,009 <0,05) while the visibility variable has no significant effect on brand image (p-value 0.621 <0.05) and the power variable does not significantly influence the brand image (p-value 0.726 <0.05). The simultaneous variables of visibility, credibility, attraction and power have a significant effect on brand image (p-value 0,000 <0,05). The coefficient of determination (R2) with a gain of 0.584. Thus it can be concluded that the influence of independent variables is 58%. Keywords : Celebrity Endorse, Brand Image, Pond’s Men Energy Charge.